Thermodynamic analysis on oil palm biomass Cogeneration Plant - Talib, N. (Asian Research Publishing Network, 2016)
Growth in energy demand has become a major concern in the earth today. The shortage of main fuel derived from conventional fossil fuel has led to an increasing demand on new source of energy, the renewal energy. Renewal energy is the proven alternative to overcome these problems. For the case of palm oil mills, the palm fibre and shell are the main source of renewal energy and cogeneration are adopted in exploiting these renewal energy sources. For this case study, the potential of these renewal energy sources were being investigated using thermodynamic analysis. Sie-Manggaris Palm Oil Mill Cogeneration Plant has been selected as a case-study model. From the analysis, it was found that the available fuel, which was accounted only palm fiber and shell, was able to generate steam up to 45,000 kg h-1. This would give the potential energy production of 157 GJ h-1 and easily able to fulfill the need of the utility requirement for the entire plant. Although, the current configuration of the existing cogeneration system would impose the deficit power of 4 kWh ton FFB-1 and has to be supported using diesel generator set at the diesel consumption rate of 0.8 L ton FFB-1. The current boiler capable to convert 1 kg of fuel to 3.35 kg of steam with the turbine steam rate at 30 kg kWh-1. Retrofit design of the existing plant is necessary in order to overcome the low energy efficiency. Substantial amount of power production could be generated if utilizing the high-energy efficient equipment. Â© 2006-2016 Asian Research Publishing Network (ARPN).